Strategic Adjustment and Performance Evaluation in the Context of Digital Transformation - Lin, Yilan (Simen Owen Academic Proceedings Series, 2025)
This study explores the impact of digital transformation on corporate strategic adjustment and performance by employing multi-industry panel data, regression analysis, Data Envelopment Analysis (DEA), and panel modeling. The empirical results demonstrate a significant positive association between digital transformation inputs-such as R&D expenditure, IT investment, and employee training-and financial performance indicators, including return on assets (ROA) and return on equity (ROE). The DEA findings reveal notable efficiency disparities among industries, with information technology enterprises outperforming those in manufacturing and service sectors. This suggests that industry-specific capabilities play a crucial role in shaping the effectiveness of digital transformation initiatives. Furthermore, the panel data analysis confirms that digital investment yields sustained long-term benefits, particularly within innovation-driven industries where cumulative advantages emerge progressively over time. The results emphasize that achieving successful digital transformation extends beyond mere technological adoption; it requires strategic realignment, enhanced organizational agility, and implementation approaches tailored to contextual conditions. Overall, this research offers practical insights for enterprises seeking to strengthen competitiveness and attain sustainable growth within the digital economy. It also provides valuable guidance for policymakers in promoting digital adoption across industries through targeted support measures, workforce skill development, and infrastructure enhancement. By integrating both financial and non-financial performance indicators, this study contributes to advancing theoretical understanding and developing practical frameworks for effectively managing digital transformation in diverse industrial settings.